A Review Study on Biocompatible Improvements of NiTi-based Shape Memory Alloys - Mohammed, Safar Saeed; Kök, Mediha; Qader, Ibrahim Nazem; Coşkun, Meltem (My University, 2021)
NiTi-based shape memory alloys (SMAs) have many applications, especially for implantation, however since they are not a passive material so it is important to investigate them from different biocompatible perspectives. In this study, we introduced the important physical characteristics of NiTi alloys, then we explained different biocompatible terminologies, including carcinogenic, genotoxic, cytotoxicity, mutagenic, allergic, and corrosivity. We collected some important previous works that investigated the biocompatibility of NiTi-based SMAs and the different techniques used for improving the alloy and diminishing the hazard due to Ni-leakages.
Keywords: Biocompatibility; NiTi; toxicity; Carcinogenic; shape memory alloys; Mutagenic